Developing Entrepreneurial Competencies in Coffee Farming: Strategic Approaches for Kepahiang Regency - Tmbul Rasoki; Ana Nurmalia (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
National coffee consumption by Indonesians has consistently increased over the past five years, while exports of raw coffee beans have declined. On the other hand, exports of ground coffee, coffee beverages, and instant coffee have grown, except for a sudden drop in instant coffee exports in 2019. Research on entrepreneurial competencies reveals that eleven indicators range from low to moderate levels, with the weakest being the ability to seize business opportunities. Analyzing internal and external factors is crucial to addressing the moderate-to-low entrepreneurial competencies of coffee farmers in Kepahiang Regency, followed by formulating strategies using the SWOT approach. The study recommends a conservative WO (Weaknesses-Opportunities) strategy to overcome internal weaknesses and optimize opportunities by enhancing technical training and education in coffee cultivation, leveraging natural resources, and improving decision-making and creativity to manage microenterprises diversity effectively. This research has broader relevance to agribusiness development by providing strategic insights that can enhance the competitiveness and sustainability of the coffee sector in the global market.